2007
DOI: 10.1097/gme.0b013e3180587eb5
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen modulation of epithelial permeability in cervical-vaginal cells of premenopausal and postmenopausal women

Abstract: The results suggest that the transient estrogen decrease in RLIS is mediated by modulation of actomyosin, and it is affected by the aging process. In contrast, the late persistent decrease in RTJ is mediated by occludin degradation and is unrelated to aging.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 24 publications
0
21
0
2
Order By: Relevance
“…The vaginal epithelium imparts two important functions in vaginal lubrication: permeability and the production of mucin glycoproteins, both believed to be regulated by estrogen [28]. Untreated diabetic animals had reduced estradiol levels and an atrophic epithelium, both of which may potentially contribute to reduced vaginal lubrication as reported in diabetic women.…”
Section: Discussionmentioning
confidence: 88%
“…The vaginal epithelium imparts two important functions in vaginal lubrication: permeability and the production of mucin glycoproteins, both believed to be regulated by estrogen [28]. Untreated diabetic animals had reduced estradiol levels and an atrophic epithelium, both of which may potentially contribute to reduced vaginal lubrication as reported in diabetic women.…”
Section: Discussionmentioning
confidence: 88%
“…The increased immunolocalization of steroid hormone receptors in the atrophic diabetic epithelium may represent a biological process of compensation to maintain the epithelium at a functioning basal state in the diabetic milieu and prevent any further tissue involution. Normal stratification of the epithelium protects the vaginal wall from abrasions and trauma during coitus and plays a role in permeability and the production of mucinous glycoproteins to lubricate the luminal surface of the vagina [36].…”
Section: Discussionmentioning
confidence: 99%
“…In other studies, Gorodeski examined the effects of hormones on TER in human normal epithelial vaginal-ectocervical cells from premenopausal and postmenopausal women and found that E 2 induced an early transient decrease in TER through a remodeling of occludin. 54,55 …”
Section: Sex Hormone Effects On Epithelial Cellsmentioning
confidence: 99%